EVALUATION OF EQUIVALENCY FROM STRUCTURAL POSITIONS TO FUNCTIONAL POSITIONS IN OPTIMIZING DUTIES, FUNCTIONS, AND CAREER DEVELOPMENT AT BKPSDMD JAMBI CITY - Farid, Miftah; Rosita, Sry; Adriani, Zulfina (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
Bureaucratic simplification through the structural-to-functional position equivalency policy represents one of the most transformative civil service reforms in Indonesia. This study examines the extent to which this policy has optimized the duties, functions, and career development of nine civil servants at the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Daerah (BKPSDMD) Kota Jambi who underwent the equivalency process. Employing a qualitative descriptive case study design, data were collected through in-depth semi-structured interviews with all nine transitioned officials, two HR managers, and the agency head, supplemented by three months of non-participant observation and systematic documentary analysis of performance records from 2020 to 2023. The findings indicate that while the initial transition period generated genuine challenges—including role ambiguity, loss of formal managerial authority, career pathway uncertainty, technical competency gaps, and psychological adjustment to perceived status change—these difficulties were confined to the first three to six months and proved entirely surmountable. Once officials adapted to their functional roles, performance outcomes improved markedly: the proportion rated 'Good' or 'Very Good' rose from 56 percent pre-transition to 89 percent post-adaptation. Career development engagement also intensified, with annual training participation increasing by 65 percent, the domain-specific technical training share rising from 33 percent to 69 percent, and eight of nine officials on track for functional grade promotion within three years. The study concludes that the equivalency policy has fulfilled its core objectives at BKPSDMD Kota Jambi, and that the quality of institutional transition support—particularly peer mentoring, targeted technical training, and individualized career counseling—is the decisive factor determining the speed and quality of adaptation outcomes.